(untitled) (INTERNATIONAL SEMINAR, 2025)
Waqf (Islamic endowment), as a legal act within the framework of Sharia, holds significant dual dimensions: a deep spiritual dimension and a profound socio-economic dimension aimed at realizing the economic potential of assets for general welfare. However, the common practice of wakaf siri (informal waqf), established through oral declarations or unauthentic deeds, leaves a significant portion of waqf assets in Indonesia in a precarious legal position. This study addresses the legal implications of wakaf siri and analyses the urgency of formal legal protection. Using a normative legal approach, this research examines Law Number 41 of 2004 concerning Waqf and related judicial precedents. The findings indicate that wakaf siri lacks legal certainty, making the assets susceptible to disputes, transfer of ownership, and potential misuse. The judicial mechanism of Isbat Wakaf (legal ratification or confirmation of waqf in the Religious Court) is identified as the critical instrument to formalize and validate these previously informal endowments. Effective implementation of the Waqf Law, particularly the mandatory registration and certification of waqf assets, is crucial to transitioning informal waqf to a legally secure status, thus guaranteeing the asset’s perpetuity and achieving its intended social welfare goals.